Modelling and simulation of the quantum ranging and positioning system. (1st November 2020) - Duan, Shiqi; Cong, Shuang; Zou, Zisheng; Wang, Hailun; Song, Yuanyuan
ABSTRACT: An integrated simulation model of the quantum ranging and positioning system (QRPS) is analyzed and built as a means for illustrating the inner structure and working principle of the system. The QRPS is composed of an acquisition, tracking and pointing (ATP) module and a coincidence counting module. In the ATP module, an accurately controlled position system model with noise and disturbance is built, and a model reference adaptive control (MRAC) strategy with state filtering is designed to estimate the system state, the noise and disturbance, and accurately track the position state. In the coincidence counting module the time difference of arrival (TDOA) of the entangled photon pairs is dealt with and obtained. Numerical experiments are implemented to verify the system performance. With a user-friendly interface, the model we proposed can provide theoretical guidance for system integration of the QRPS.